Comparision of treatment outcomes in isolated injuries of anterior cruciate ligament (ACL) and injuries of ACL connected with damages of menisci, conducted with use of KOOS scale - Piotr Piech; Paweł Polak; Maciej Kozioł; Karolina Rasoul; Jadwiga Kozioł; Małgorzata Neścior; Robert Łuczyk (Kazimierz Wielki University, 2017)
Introduction: Anterior cruciate ligament (ACL) rupture is one of the most common knee injuries. Such trauma is caused by sudden hyperextension and internal rotation above physiological range of movement. It is most commonly diagnosed in young and physically active people. ACL injury is often accompanied by damages of menisci. Aim: The aim of this study was to compare treatment outcomes in patients with isolated rupture of ACL and with both ACL and menisci damages Materials and Methods: In this retrospective study subjective opinions of 46 patients of Orthopedics and Traumatology Clinic of SPSK4 in Lublin were evaluated. Subjects were 19-59 years old, 28 of them had isolated ACL injury, while 18 suffered also with menisci damages. The study was conducted using KOOS questionnaires. Complications, hospitalization time and reconstruction technique were also taken into account. Results: Maximum rating in KOOS scale is 100 points for each of the parameters. This rating characterizes the most favorable state. For pain average rating in isolated ACL injury was 82,31 while in ACL injury with meniscus damage it was 84,37. For other parameters results were respectively: quality of life - 63,59 and 61,81; remaining symptoms 74,57 and 74,09; daily activities 86.61 and 83.84;  sport 70.71 and 65.56. The data have been developed with the help of non-compliance test chi2. Conclusions: The results of the work show that there is a correlation between the type of injury and the assessment of the patient in three parameters: remaining symptoms, daily functioning and sport. The other two parameters (quality of life, pain) were irrelevant.